MEMBANGUN HARMONI ANTARBUDAYA MELALUI KONSELING MULTIKULTURAL: Studi Kasus Mahasiswa Bimbingan dan Konseling - Maulinsari, Putri Gusti; Nurlela; Sari, Syska Purnama; Surtiyoni, Endang; Putri, Ramtia Darma (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Multicultural counseling is one of the most important approaches in the context of education in Indonesia, especially in schools that have cultural diversity such as BK students of the class of 2024. In this journal, it will be discussed how multicultural counseling can play a role in building intercultural harmony in the campus environment. Data shows that Indonesia is a country with more than 300 ethnic groups, each of which has a different culture and values (BPS, 2021). Thus, the challenges faced by students in creating an inclusive and harmonious environment are very large. Through a case study of BK students of the class of 2024, this article aims to explore the positive impact of multicultural counseling for students, especially for those from minority groups